Iot based intelligent route selection of wastage segregation for smart cities using solar energy. (August 2021) - Ashwin, M.; Alqahtani, Abdulrahman Saad; Mubarakali, Azath
Abstract: The waste management is a major problem all over the world. The smart is an innovative automated device for the separate collection of used absorbent hygiene products. The Automatic Intelligence Smart Bin helps to solve waste management problem in smart cities. The smart bin will play a important role in smart cities. The smart lifestyle begins with cleanliness environment within the city which originates with smart bin. The smart bin utilized HC-SR04 Ultrasonic Sensor is used to identify human being and TowerPro SG90 Servo Motor is used to open/close the smart bin lid automatically. The Arduino Uno microcontroller was used to control the smart bin overall functionality. The smart bin separates dry/wet garbage collection using IoT sensor within the smart bin. The smart bin is full up to 80% then the microcontroller sends warning message to garbage collector automatically. The top of the smart bin solar panel is fixed, which is used to collect energy from sun. The collected energies are stored in the battery bank which is used to operate smart bin automatically. The applications of smart bins are shopping malls, Colleges/University campus, Railway stations, Tourist areas, Parks etc.